Depictions of Violence Racism in Ron Stallworth‘s Novel Black Klansman - Rifyatul Azizah; Sudirman Maca; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
The objectives of this study were to identify the depictions of violence racism and identify the impact of violence racism on African-America society in“Black Klansman” novel by Rons Stallworth.The data source used in this research is Black Klansman novel. In analyzing the data, the writer used a qualitative descriptive research method through sociological approach. The data were obtained by using reading, identified, noting and quoting, and collecting data techniques to classify the racism and the impact of racism in the novel Black Klansman by Swingewood and Setiadi theories with his classification of violence in narrow and broad sense. The result of this research there were 13 data that depicted of violence racism in “Black Klansman” novel by Ron Stallworth. 5 data contained the violence racism in narrow sense, 8 data of the violence racism in broad sense, and there were 9 data which include the impact of violence racism.